Polymer-coated Pt / C catalyst with vacancy interlayer as well as preparation method and application of polymer-coated Pt / C catalyst
The in-situ polymerization coating method forms a polymer coating layer with vacancies on the surface of the Pt/C catalyst, which solves the problem of the catalyst being susceptible to poisoning under fuel cell operating conditions, improves the stability and anti-poisoning performance of the catalyst, and The preparation process is simplified.
Patent Information
- Application Number
- CN202411444742.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-16
AI Technical Summary
The existing Pt/C catalysts are susceptible to poisoning of -SO3H in Nafion under fuel cell conditions, resulting in catalyst deactivation, and the carbon shell coating method has a sintering process, resulting in activity loss and complex preparation.
Adopt the in -situ aggregation covering method, cover the nano -cu (OH) 2 front -drive product product on the surface of the PT/C catalyst, and on its surface in original polymer amino polymer film. , Form a PT/C catalyst covered with a polymer with a vacant expansion.
Improve the anti-poisoning properties and stability of the catalyst, reduce the reunion and dissolution of PT particles, enhance the spatial block effect on-SO3H, avoid activity loss, and simplify the preparation process.
Smart Images

Figure CN119361721A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a polymer-coated Pt / C catalyst with a vacancy interlayer, a preparation method and an application thereof, and belongs to the technical field of electric catalysts for fuel cells and their preparation. Background Art
[0002] Fuel cells are ideal for next-generation energy conversion due to their readily available raw materials, pollution-free products, and high theoretical energy density. Proton exchange membrane fuel cells (PEMFCs), with their moderate operating temperatures, simple reactions, and low cost, are currently the most promising fuel cell system for powering next-generation transportation equipment.
[0003] The oxygen reduction reaction (ORR) at the cathode of PEMFCs is a bottleneck limiting the system's performance. This is due to slow ORR kinetics and catalyst deactivation and poisoning after long cycles. Although Pt-based catalysts are relatively expensive, they remain the most commercially available and perform best. Therefore, optimizing their ORR performance holds significant commercial value. A common problem with PEMFCs is that the high activity exhibited by the catalyst in rotating disk electrode (RDE) tests cannot be replicated in actual PEM tests. This is because under actual PEM operating conditions, metal atoms in Pt particles are more likely to dissolve and nanoparticles to aggregate at high current densities, resulting in a reduction in the electrochemical active area (ECSA). Furthermore, due to Pt's high surface activity, it adsorbs a variety of toxic substances, leading to catalyst deactivation. In RDE tests, all Pt particles come into direct contact with protons and oxygen through ultrapure water. However, in PEM tests, the Pt catalyst is tightly bound to a perfluorosulfonic acid ionomer layer (Nafion). Proton transport and oxygen diffusion can only reach the catalyst surface through the Nafion, resulting in greater diffusion resistance. Furthermore, the sulfonic acid groups (-SO3H) in the Nafion layer can severely poison the Pt sites, significantly reducing the mass activity density (SD). Therefore, improving the stability and anti-poisoning properties of Pt / C catalysts is a key technology for achieving long-life PEMFC applications.
[0004] Surface coating is a commonly used method to improve catalyst stability and interface modification. At present, the coating of Pt-based catalysts is mainly carbon shell coating. This coating layer reduces the agglomeration and dissolution of Pt particles by limiting the migration of active sites. At the same time, it physically isolates the contact between Pt and the electrolyte, reducing the adsorption and desorption of toxic molecules on the Pt surface. However, this method has certain problems: First, the coated carbon shell must undergo a sintering process. During the sintering process, Pt particles will inevitably agglomerate, resulting in a certain loss of activity. Secondly, the thickness and structure of the sintered carbon shell are difficult to control. If it is too thick, the active sites will be masked, and if it is too thin, there will be no protection effect, resulting in a complicated preparation process. Finally, there are few functional groups on the surface of the carbon shell, making it difficult to achieve selective passage of molecules, so the anti-toxicity is relatively weak.
[0005] In summary, it is crucial to develop a coating method that does not require sintering, exhibits high mechanical strength, and contains adsorbable functional groups. Furthermore, since polymer coating is already widely used to modify positive and negative electrode materials in batteries, and the structure and physical and chemical properties of the coating layer can be precisely controlled by selecting the functional groups in the monomers and the degree of polymerization, further applying this method to coating Pt-based catalysts in fuel cells holds great promise. Summary of the Invention
[0006] Aiming at the problem that -SO3H in Nafion is adsorbed on the Pt surface in the existing Pt / C catalyst under fuel cell operating conditions, resulting in catalyst poisoning, the present invention provides a polymer-coated Pt / C catalyst with a vacancy interlayer, a preparation method and an application thereof.
[0007] The technical solution of the present invention:
[0008] One of the objects of the present invention is to provide a method for in-situ polymerization coating of a Pt / C catalyst, the method specifically comprising the following steps:
[0009] (1) Pt / C catalyst, buffer solution and anhydrous ethanol were mixed and ultrasonically dispersed uniformly, and then an inorganic copper source was added. After adjusting the pH to 9.4 with ammonia water, the reaction was stirred. After the reaction was completed, the obtained product was washed and dried to obtain a precursor product of Cu(OH)2-coated Pt / C catalyst;
[0010] (2) mixing the precursor product obtained in (1), a buffer solution and an amino polymer monomer, adjusting the pH to 7.5-9, stirring and reacting at 0-20° C. for 1-2 h, filtering the obtained product with distilled water several times to remove residual polymer monomers, and freeze-drying the product using liquid nitrogen to obtain a product with an in-situ polymer film coated on the surface of the precursor product;
[0011] (3) Adding HClO4 to the product obtained in (2), heating, stirring, and refluxing to dissolve the Cu(OH)2, and freeze-drying the product using liquid nitrogen after the reflux to obtain a polymer-coated Pt / C catalyst having a vacancy interlayer.
[0012] It is further defined that the Pt / C catalyst in (1) is a commercial Pt / C catalyst with a loading of 40%.
[0013] It is further defined that the buffer in (1) is Tris(hydroxymethyl)aminomethane at a concentration of 1.2 mg / mL.
[0014] It is further defined that the mass volume ratio of the Pt / C catalyst, the buffer solution and the anhydrous ethanol in (1) is 20 mg:10 mL:5 mL.
[0015] It is further defined that the inorganic copper source in (1) is copper nitrate, copper chloride or copper sulfate, and the mass of the added Cu element is 2-8% of the mass of the Pt / C catalyst.
[0016] It is further defined that the drying treatment in (1) is: vacuum drying at 120°C for 6 hours.
[0017] It is further defined that the amino polymer monomer in (2) is acrylamide, N-vinylacetamide, catecholethylamine or aniline.
[0018] It is further defined that the buffer in (2) is Tris(hydroxymethyl)aminomethane at a concentration of 1.2 mg / mL.
[0019] It is further defined that the mass volume ratio of the precursor product, buffer and amino polymer monomer in (2) is 20 mg:10 mL:(20-30) mg.
[0020] It is further defined that the degree of polymerization of the amino polymer monomer in (2) is 50 to 70%.
[0021] It is further defined that the concentration of HClO4 in (3) is 0.1 M and the heating and stirring reflux temperature is 60°C.
[0022] It is further defined that the mass volume ratio of the product obtained in (2) in (3) to HClO4 is 15 mg:45 ml.
[0023] A second object of the present invention is to provide a polymer-coated Pt / C catalyst with a vacancy interlayer prepared by the above method. Specifically, the catalyst has a Pt / C catalyst as the core, a polymer coating layer is in situ coated on the core surface, and a vacancy interlayer is formed between the core and the polymer coating layer.
[0024] It is further defined that the thickness of the polymer coating layer is 1-3 nm.
[0025] It is further defined that the thickness of the vacancy interlayer is less than 2 nm.
[0026] The third object of the present invention is to provide an application of the above catalyst, specifically as a cathode catalyst for a fuel cell.
[0027] Beneficial effects:
[0028] The present invention first uniformly coats the surface of a commercial Pt / C catalyst with a layer of nano-Cu(OH)2 precursor by controlling the copper source content and pH. Secondly, by regulating the pH and reaction temperature, amino-containing polymer monomers are in situ polymerized on the surface of the precursor using simple stirring, resulting in a surface coating with a polymer film rich in amino groups that selectively isolates -SO3H, which does not require sintering. Finally, a sacrificial hard template is used to create a vacant interlayer between the coating layer and the catalyst, increasing the steric hindrance effect between -SO3H and the catalyst. Compared with existing technologies, this method has at least the following advantages:
[0029] (1) The present invention successfully prepared a commercial platinum-carbon catalyst coated with a polymer having a vacancy interlayer and specific functional groups by coating the surface of a sacrificial hard template and then dissolving the template. The coating layer and its vacancy interlayer have a certain physical isolation effect, inhibiting the agglomeration of Pt particles and reducing the adsorption of -SO3H on the catalyst surface through the steric effect; at the same time, the amino group carried by the coating layer has a certain alkalinity, and through the Coulomb force between charges, it has a certain characteristic adsorption capacity for the acidic group -SO3H, thereby greatly improving the anti-poisoning performance of the catalyst.
[0030] (2) The present invention selects an amino polymer as the polymer coating layer, and utilizes the amino group in the amino polymer and the aromatic ring in the skeleton to form a conjugated structure, which is beneficial to the transition and transmission of electrons. At the same time, the amino group is partially in a charged state in the acidic system, and then there is electron transfer on its surface. The two work together to make the amino polymer have excellent conductivity. At the same time, the presence of a large number of structurally strong bonds such as CC bonds and CN bonds in its polymer system makes the molecular structure stable. The amino group, as an endothermic group, further alleviates the thermal decomposition reaction of the polymer, making its decomposition temperature higher than 200°C. The actual operating temperature of the proton exchange membrane fuel cell is 80°C, which is far below the lower limit of thermal decomposition. Therefore, the coating layer has excellent conductivity and high thermal stability under fuel cell operating conditions.
[0031] (3) In the present invention, the polymer coating layer is not directly polymerized on the catalyst surface. Instead, a sacrificial Cu(OH)2 template is added between the catalyst and the polymer. Further etching creates nanoscale vacancies between the catalyst layer and the coating layer, thereby enhancing the steric hindrance effect and improving the isolation effect of the coating layer on the -SO3H poisoned catalyst surface.
[0032] (4) The coating method provided by the present invention does not require sintering. It synergistically improves the anti-poisoning performance of the catalyst through ionic adsorption and physical isolation effect while ensuring that the catalyst activity is almost unchanged. In addition, the coating layer structure can be precisely controlled by monomer design and polymerization degree, can be prepared in large quantities, has universal applicability, and can be applied to a variety of commercial platinum-based catalysts. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 SEM images of the Pt / C@PDA catalyst prepared in Example 1 (at different magnifications);
[0034] Figure 2 CV test curves of the Pt / C@PDA catalyst prepared in Example 1, the Pt / C@C and Pt / C prepared in Comparative Example 1;
[0035] Figure 3 The LSV test curve of Pt / C in dispersions with different Nafion contents;
[0036] Figure 4 This is the LSV test curve of Pt / C@C prepared in Comparative Example 1 in dispersions with different Nafion contents;
[0037] Figure 5 This is the LSV test curve of Pt / C@PDA prepared in Example 1 in dispersions with different Nafion contents. DETAILED DESCRIPTION
[0038] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0039] In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention may also be implemented in other ways different from those described herein. Those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0040] Secondly, the term "one embodiment" or "embodiment" herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The phrase "in one embodiment" appearing in various places throughout this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive of other embodiments.
[0041] The experimental methods used in the following examples are conventional methods unless otherwise specified. All materials, reagents, methods, and instruments used, unless otherwise specified, are conventional in the art and are commercially available to those skilled in the art. All solid and liquid reagents used were of analytical grade.
[0042] Example 1
[0043] The process of preparing the Pt / C@PDA catalyst in this embodiment is as follows:
[0044] Step 1: Weigh 20 mg of a 40% loaded commercial Pt / C catalyst into a 20 mL sample bottle, add 10 mL of 1.2 mg / mL Tris buffer and 5 mL of anhydrous ethanol, seal completely, and place in a high-power ultrasonic machine for 30 minutes to obtain a uniform dispersion.
[0045] Step 2: Place the sample bottle containing the dispersion on a magnetic stirrer, add 4.56 mg of Cu(NO3)2·3H2O, stir for 60 minutes, and after it is fully dissolved, use ammonia water to adjust the pH of the solution to 9.4, then continue stirring for 12 hours. After stirring, wash the product and vacuum dry it at 120°C for 6 hours to obtain a Cu(OH)2-coated Pt / C catalyst.
[0046] Step 3: Add 20 mg of the product of step 2 to a 20 mL sample bottle, add 10 mL of 1.2 mg / mL tris(hydroxymethyl)aminomethane buffer, use catecholethylamine as the polymer monomer, use an ice bath to control the polymerization temperature at 0-10 ° C, use ammonia water to adjust the pH value of the dispersion to 8.3-8.7, the mass ratio of the polymer monomer to the product of step 2 is 30 mg: 20 mg, maintain the temperature and pH constant, and continue stirring for 1.5 hours to complete the in situ polymerization coating of the catalyst surface.
[0047] Step 4: The solution obtained in step 3 was filtered three times with distilled water to wash away the buffer solution and residual polymerization monomers. The resulting product was placed in a ziplock bag and quickly frozen with liquid nitrogen, followed by freeze drying for 24 hours. The resulting powder was the polydopamine-coated platinum-carbon catalyst.
[0048] Step 5: Add 15 mg of the product obtained in step 4 to 45 mL of 0.1 M HClO4, stir at 60°C for 6 hours, reflux to dissolve the Cu(OH)2 in the interlayer, place the product after reflux in a ziplock bag for quick freezing with liquid nitrogen, and freeze-dry for 24 hours. The resulting powder is the final product: a commercial Pt / C catalyst coated with polydopamine having a vacancy interlayer, referred to as Pt / C@PDA.
[0049] Example 2
[0050] The process of preparing the Pt / C@PDA catalyst in this embodiment is as follows:
[0051] Step 1: Weigh 20 mg of a 40% loaded commercial Pt / C catalyst into a 20 mL sample bottle, add 10 mL of 1.2 mg / mL Tris buffer and 5 mL of anhydrous ethanol, seal completely, and place in a high-power ultrasonic machine for 30 minutes to obtain a uniform dispersion.
[0052] Step 2: Place the sample bottle containing the dispersion on a magnetic stirrer, add 4.56 mg of Cu(NO3)2·3H2O, stir for 60 minutes, and after it is fully dissolved, use ammonia water to adjust the pH of the solution to 9.4, then continue stirring for 12 hours. After stirring, wash the product and vacuum dry it at 120°C for 6 hours to obtain a Cu(OH)2-coated Pt / C catalyst.
[0053] Step 3: Add 20 mg of the product of step 2 to a 20 mL sample bottle, add 10 mL of 1.2 mg / mL tris (hydroxymethyl)aminomethane buffer, use aniline as the polymer monomer, use an ice bath to control the polymerization temperature at 0-10°C, use ammonia water to adjust the pH value of the dispersion to 7.3-7.8, the mass ratio of the polymer monomer to the product of step 2 is 30 mg: 20 mg, add 1 mL of 3% concentration hydrogen peroxide solution as a polymerization initiator, maintain the temperature and pH constant, and continue stirring for 1.5 hours to complete the in situ polymerization coating on the catalyst surface.
[0054] Step 4: The solution obtained in step 3 was repeatedly filtered three times with distilled water to wash away the buffer solution and residual polymerization monomers. The obtained product was placed in a ziplock bag and quickly frozen with liquid nitrogen, and then freeze-dried for 24 hours. The obtained powder was a polyaniline-coated platinum carbon catalyst.
[0055] Step 5: 15 mg of the product obtained in step 4 was placed in 45 mL of 0.1 M HClO4, stirred at 60°C for 6 h, and refluxed to dissolve the Cu(OH)2 in the interlayer. The product after reflux was placed in a ziplock bag and quickly frozen with liquid nitrogen. After freeze-drying for 24 h, the resulting powder was the final product, a commercial Pt / C catalyst coated with polyaniline having a vacancy interlayer.
[0056] Comparative Example 1
[0057] The process of preparing the Pt / C@C catalyst in this comparative example is as follows:
[0058] Step 1: Weigh 20 mg of a 40% loaded commercial Pt / C catalyst into a 20 mL sample bottle, add 10 mL of 1.2 mg / mL Tris buffer and 5 mL of anhydrous ethanol, seal completely, and place in a high-power ultrasonic machine for 30 minutes to obtain a uniform dispersion.
[0059] Step 2: Place the sample bottle containing the dispersion on a magnetic stirrer, add 4.56 mg of Cu(NO3)2·3H2O, stir for 60 minutes, and after it is fully dissolved, use ammonia water to adjust the pH of the solution to 9.4, then continue stirring for 12 hours. After stirring, wash the product and vacuum dry it at 120°C for 6 hours to obtain a Cu(OH)2-coated Pt / C catalyst.
[0060] Step 3: Add 20 mg of the product of step 2 to a 20 mL sample bottle, add 10 mL of 1.2 mg / mL tris(hydroxymethyl)aminomethane buffer, use catecholethylamine as the polymer monomer, use an ice bath to control the polymerization temperature at 0-10 ° C, use ammonia water to adjust the pH value of the dispersion to 8.3-8.7, the mass ratio of the polymer monomer to the product of step 2 is 30 mg: 20 mg, maintain the temperature and pH constant, and continue stirring for 1.5 hours to complete the in situ polymerization coating of the catalyst surface.
[0061] Step 4: The solution obtained in step 3 was filtered three times with distilled water to wash away the buffer solution and residual polymerization monomers. The resulting product was placed in a ziplock bag and quickly frozen with liquid nitrogen, followed by freeze drying for 24 hours. The resulting powder was the polydopamine-coated platinum-carbon catalyst.
[0062] Step 5: Add 15 mg of the product obtained in step 4 to 45 mL of 0.1 M HClO4, stir at 60°C for 6 hours, reflux to dissolve the Cu(OH)2 in the interlayer, place the product after reflux in a ziplock bag for quick freezing with liquid nitrogen, and freeze-dry for 24 hours. The resulting powder is a commercial Pt / C catalyst coated with polydopamine with a vacancy interlayer, referred to as Pt / C@PDA.
[0063] Step 6: Grind the powder obtained in step 5 in a mortar for 20 minutes, transfer it to a tube furnace, and heat it to 900°C at a heating rate of 30°C / min under an argon atmosphere. Anneal it at this temperature for 1 hour to carbonize the catalyst surface coating. The resulting powder is a commercial platinum-carbon catalyst coated with nitrogen-doped carbon, abbreviated as Pt / C@C.
[0064] Application Examples
[0065] (1) The surface micromorphology of Pt / C@PDA prepared in Example 1 was characterized. Figure 1As shown in the figure, it can be seen that the surface of the Pt particles is evenly covered by a coating layer with a thickness of 1.5 nm, and the coating layer does not undergo structural collapse due to the dissolution of the Cu(OH)2 hard template.
[0066] (2) The CV test curves of the Pt / C@PDA catalyst prepared in Example 1, the Pt / C@C prepared in Comparative Example 1, and the raw material Pt / C are as follows: Figure 2 As shown, the test atmosphere is 0.1M HClO4 solution saturated with argon, the voltage range is 0.03~1.2V, and the scan rate is 50mV / s. Figure 2 It can be seen that the hydrogen zones of the two curves of the commercial Pt / C catalyst coated with polydopamine having a vacancy interlayer prepared in Example 1 without a sintering process and the commercial Pt / C catalyst almost overlap, indicating that the in-situ polymerization coating does not reduce the electrochemical active area of the catalyst and there is almost no loss of activity. The polymer coating layer of the Pt / C@PDA prepared in Example 1 was further sintered, that is, the current density in the hydrogen zone of the CV curve of the Pt / C@C catalyst obtained in Comparative Example 1 decreased significantly, indicating that the electrochemical active area of the catalyst has become smaller and the current density in the double layer region has decreased, indicating that after sintering, some of the mesopores of the catalyst powder have been blocked, which reduces the equivalent capacitance of the catalyst. Comparison of the CV curves of Example 1 and Comparative Example 1 shows that the unsintered amino polymer-coated platinum carbon catalyst has a higher catalytic potential.
[0067] (3) The test of the catalyst's anti-poisoning performance was expressed as the loss of half-wave potential in the LSV test curve of the catalyst in dispersions with different Nafion content (Group 2, in which the proportion of Nafion solution was increased 10 times compared to Group 1, was used to explore the tolerance of the platinum-carbon catalyst to -SO3H group poisoning before and after coating). The dispersion composition ratio of Group 1 was catalyst: water: isopropanol: 5% Nafion solution (4 mg: 3 mL: 1 mL: 4 mL). The dispersion composition ratio of Group 2 was catalyst: water: isopropanol: 5% Nafion solution (4 mg: 3 mL: 1 mL: 40 mL).
[0068] The raw material Pt / C catalyst was subjected to LSV test in two groups of dispersions between 0.03 and 1.2 V at a sweep rate of 10 mV / s. The test results are as follows Figure 3 As shown by Figure 3 It can be seen that when the Nafion content increases dramatically, the half-wave potential of the Pt / C catalyst loses a lot, which indicates that the Pt / C catalyst without coating layer has poor tolerance to -SO3H.
[0069] The Pt / C@PDA catalyst prepared in Example 1 was subjected to LSV test in two groups of dispersions at a sweep rate of 10 mV / s between 0.03 and 1.2 V. The test results are shown in Figure 2. Figure 5As shown by Figure 5 It can be seen that when the Nafion content increases dramatically, the half-wave potential of the catalyst has almost no loss compared to the Pt / C catalyst, indicating that the amino polymer coating layer greatly improves the catalyst's tolerance to -SO3H. At the same time, compared with the original Pt / C catalyst, the initial half-wave potential of the catalyst has almost no change (0.87 vs. 0.87V). The coating layer will not reduce the initial activity of the catalyst and avoids the activity loss caused by Pt particle agglomeration.
[0070] The Pt / C@C catalyst prepared in Comparative Example 1 was subjected to LSV tests in two groups of dispersions at a sweep rate of 10 mV / s between 0.03 and 1.2 V. The test results are shown in the figure. Figure 4 As shown by Figure 4 It can be seen that the loss of half-wave potential of the sintered Pt / C@C catalyst becomes smaller when the Nafion content increases dramatically compared with the Pt / C catalyst, indicating that the nitrogen-doped carbon coating layer helps to improve the catalyst's tolerance to -SO3H. However, after sintering, the initial half-wave potential of the catalyst is significantly reduced compared with the original catalyst (0.80 vs. 0.87 V), indicating that the Pt particles have a certain degree of agglomeration and the activity of the catalyst has been greatly reduced.
[0071] Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.
Claims
1. A method for in-situ polymerization coating of Pt / C catalyst, characterized in that: include: (1) Pt / C catalyst, buffer solution and anhydrous ethanol are mixed and dispersed uniformly by ultrasonication, and then an inorganic copper source is added, and the pH is adjusted to 9.4 with ammonia water, and then stirred for reaction. After the reaction is completed, the obtained product is washed and dried to obtain a precursor product of Cu(OH)2-coated Pt / C catalyst; (2) mixing the precursor product obtained in (1), a buffer solution and an amino polymer monomer, adjusting the pH to 7.5-9, stirring the mixture at 0-20° C. for 1-2 h, filtering the obtained product with distilled water for multiple times to remove residual polymer monomers, and freeze-drying the product using liquid nitrogen to obtain a product having a polymer film in situ coated on the surface of the precursor product; (3) Add HClO4 to the product obtained in (2), heat and stir under reflux to dissolve Cu(OH)2, and freeze-dry using liquid nitrogen after reflux to obtain a polymer-coated Pt / C catalyst with a vacancy interlayer.
2. The method according to claim 1, characterized in that (1) The Pt / C catalyst is a commercial Pt / C catalyst with a loading of 40%, and the buffer is tris(hydroxymethyl)aminomethane with a concentration of 1.2 mg / mL; the mass volume ratio of the Pt / C catalyst, the buffer and anhydrous ethanol is 20 mg:10 mL:5 mL.
3. The method according to claim 1, characterized in that (1) The inorganic copper source is copper nitrate, copper chloride or copper sulfate, and the mass of the added Cu element is 2-8% of the mass of the Pt / C catalyst.
4. The method according to claim 1, characterized in that: (1) Medium drying treatment: vacuum drying at 120°C for 6 h.
5. The method according to claim 1, characterized in that (2) The amino polymer monomer is acrylamide, N-vinyl acetamide, catecholethylamine or aniline; the buffer is tris(hydroxymethyl)aminomethane with a concentration of 1.2 mg / mL; the mass volume ratio of the precursor product, the buffer and the amino polymer monomer is 20 mg:10 mL:(20-30) mg.
6. The method according to claim 1, characterized in that (2) The degree of polymerization of the amino polymer monomer is 50 to 70%.
7. The method according to claim 1, characterized in that (3) The concentration of HClO4 is 0.1 M, and the heating, stirring and reflux temperature is 60°C.
8. A polymer-coated Pt / C catalyst having a vacancy interlayer prepared by the method according to any one of claims 1 to 7, characterized in that: The catalyst uses a Pt / C catalyst as a core, a polymer coating layer is in situ coated on the surface of the core, and a vacancy interlayer is formed between the core and the polymer coating layer.
9. The catalyst according to claim 8, characterized in that The thickness of the polymer coating layer is 1-3 nm; the thickness of the vacancy interlayer is less than 2 nm.
10. Use of the catalyst according to claim 8 or 9, characterized in that: No high-temperature annealing treatment is required and it can be directly used as a fuel cell cathode catalyst.
Citation Information
Patent Citations
Method for preparing efficient stable fuel cell catalyst
CN103495432A
Preparing method for high-activity and high-stability composite catalyst for fuel cells
CN105107541A
Transition metal nanoparticle catalyst coated with graphitized carbon layer and preparation method of transition metal nanoparticle catalyst
CN113410475A
Platinum-cobalt alloy catalyst, preparation method and application thereof
CN115133050A
In-situ preparation method of catalyst for electrocatalytic reduction of CO2
CN116905040A